Patterns of neurobehavioral functioning in school-aged survivors of neonatal jaundice and hypoxic-ischemic encephalopathy in Kilifi, Kenya: a cross-sectional study - Magai, DN; Newton, CR; Mwangi, P; Koot, HM; Abubakar, A (F1000Research, 2019)
Background: Studies in high-income countries have reported that school-aged children who survive neonatal jaundice (NNJ) and hypoxic-ischemic encephalopathy (HIE) develop long-term neurocognitive problems. However, less is known about the patterns of functioning in school-aged survivors of NNJ and HIE in sub-Saharan Africa. This study examined patterns of functioning in school-aged children who survived NNJ and HIE in Kilifi, Kenya. Methods: This is a cross-sectional study that included 107 survivors of NNJ/HIE (64 with NNJ, 43 with HIE), aged 6-12 years, admitted to Kilifi County Hospital on the Kenyan Coast. The Gross Motor Function Classification System (GMFCS), Adapted Communication Profile, Raven’s Coloured Progressive Matrices (RCPM) and an epilepsy screening tool were used to assess gross motor function, communication function, intellectual functioning, and epilepsy, respectively. Results: Most of the survivors of NNJ (95.2%) and HIE (95.3%) had no impairments in gross motor functioning. A small percentage of the children in the NNJ and HIE groups had profound problems in their communication (4.7% and 4.7%); expressive communication function (4.7% and 4.7%); social functions (3.1% and 2.3%); receptive communication (4.7% and 2.3%); and communicative effectiveness (4.7% and 2.3%). Cognitive impairment was reported in 10.9% and 11.9% for NNJ and HIE survivors, respectively. Active epilepsy was detected in 1.6% of survivors of NNJ and 2.3% of survivors of HIE. All children had normal hearing and visual functioning except one participant who presented with mild visual acuity problems. Conclusions: Most school-aged children who survive with NNJ and HIE have normal motor and communication function; however, one in ten are likely to present with lowered intellectual functioning compared to the normative sample.